Ventricular arrhythmias in patients with immune checkpoint inhibitor myocarditis. (14th October 2021) - Hassan, M; Fradley, M G; Drobni, Z D; Mahmood, S S; Nohria, A; Thuny, F; Michel, C; Mahmoudi, M; Thavendiranathan, P; Garcia De Yebenes Castro, M; Afilalo, J; Nicolas, E Z; et al.
Abstract: Background: Immune checkpoint inhibitor (ICI)-associated myocarditis is associated with a markedly increased risk of morbidity and mortality. The occurrence of ventricular arrhythmias (VA) in patients with ICI-associated myocarditis has not been well characterized. Purpose: The aim of this study was to determine the characteristics and risk factors for severe VA in patients with ICI myocarditis. Methods: The cohort consisted of 202 patients with ICI myocarditis. Ventricular arrhythmias were defined as a composite of sustained ventricular tachycardia and ventricular fibrillation. We used a multivariable logistic regression model to test the association between clinical variables and the development of VA. Results: From a cohort of 202 patients with ICI myocarditis (67±13 years, 35% female, 60% hypertension, 23% diabetes mellitus), 41 (20.3%) developed VA, of which, 33 had VT and 8 had VF. The median time from admission to VF was 144 hours and to VT was 72 hours. A VA occurred in 17.5% of patients with a normal LVEF, and 25% of patients with reduced LVEF. On univariate analysis, a QRS duration >110ms (OR 2.88, 95% CI 1.40 to 6.16, P=0.005) and a QTc duration >470ms were associated with an increased probability of VA (OR 2.58, 95% CI 1.23, 5.41, P=0.012). The association remained significant after adjustment for age and gender. Additionally, a longer time from admission to initiation of corticosteroids was associated with a higher probability of VA (OR 1.06, 95% CI 1.01 to 1.13, P=0.027). The association between the time from admission to administration of corticosteroids and probability of VA remained significant after adjustment for age, gender, and LVEF on admission (OR, 1.06, 95% CI 1.00, 1.13, P=0.037) where each 6-hour delay in the initiation of corticosteroids was associated with a 4% increase in the risk for VA. Conclusions: Ventricular arrhythmias are common in the setting of ICI myocarditis and are observed in patients presenting with both a preserved and a reduced LVEF. Wider QRS and longer QT at presentation and longer time from admission to initiation of corticosteroids were associated with an increased risk of VA. Funding Acknowledgement: Type of funding sources: None.